2019
DOI: 10.1182/blood.2019001545
|View full text |Cite
|
Sign up to set email alerts
|

Combined inhibition of Bcl-2 and NFκB synergistically induces cell death in cutaneous T-cell lymphoma

Abstract: Therapeutic options for cutaneous T-cell lymphoma (CTCL) are limited and curative treatment regimens are not available. Thus, new targeted and well-tolerated therapeutic approaches are urgently needed. In this respect, we have recently shown that dimethyl fumerate (DMF) inhibits NF-κB acting as a survival factor in CTCL. Similarly, inhibition of the antiapoptotic protein B-cell lymphoma 2 (Bcl-2) has been shown to induce cell death in CTCL especially when combined with histone deacetylase inhibitors. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
(88 reference statements)
1
8
0
Order By: Relevance
“…NT1721 also significantly decreased BCL2 expression in HuT78 (Figure 2A,B). However, in line with previous reports [17,34], no BCL2 mRNA or protein expression could be detected in HH cells.…”
Section: Nt1721 Downregulated Gli1 Transcription Factor In Ctcl Cellssupporting
confidence: 91%
See 2 more Smart Citations
“…NT1721 also significantly decreased BCL2 expression in HuT78 (Figure 2A,B). However, in line with previous reports [17,34], no BCL2 mRNA or protein expression could be detected in HH cells.…”
Section: Nt1721 Downregulated Gli1 Transcription Factor In Ctcl Cellssupporting
confidence: 91%
“…Adding BCL2 or BCL2/BCL-xL inhibitors to the treatment of CTCL cells with other agents (e.g., histone deacetylase or bromodomain inhibitors) synergistically increased apoptosis induction [7,17,34,45,46]. In contrast, no synergy was observed when BCL2-negative HH cells were treated with the drug combinations [17,34]. Moreover, it has been shown that antiapoptotic BCL2 proteins have a role in promoting hedgehog/GLI signaling by enhancing the turnover of a GLI antagonist, SUFU tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synergistic epigenetic-modulatory effect of histone acetylation of DNA demethylation results in global CpG methylation alterations as well as reexpression of tumor suppressor genes that was not achieved by single agent treatments (85). Preclinical and clinical investigations have demonstrated the combinatorial use of different epigenetic modulators together or in combination with other treatments (85)(86)(87)(88)(89)(90).…”
Section: Emerging Frontiers In Ctclmentioning
confidence: 99%
“…The used drug is dimethyl fumarate and inhibitor of the NFκB activation. [24,25] Further interest was directed on T-cell receptor sequencing.…”
Section: Ta B L E 1 Park Et Al Identified 55 Genes In Lymphomagenesismentioning
confidence: 99%